Factors Influencing Consumer Decisions in Consuming Environmentally Friendly Plastic Packaging in the Jabodetabek Region - Evan Mario Santoso; Puteri Dyah Nastiti; Stella Pratiwi; Albert Albert; Arief Ramdhan (Syntax Corporation Indonesia, 2024)
Plastic waste has become a significant environmental and health concern worldwide, including in Indonesia. To address this issue, the adoption of environmentally friendly packaging materials, such as biodegradable plastics, is considered a viable solution. This study aims to understand the potential switch in consumer behavior towards the use of environmentally friendly plastic packaging in Indonesia with two models of conceptual framework. Model 1 explores the relationship between Green Attitude, Perceived Environmental Responsibility, Subjective Norm, Green Product Experience, Environmental Friendliness of Companies, Perceived Behavior Control and Green Purchase Intention. Model 2 investigates the relationship between GPI and Green Purchase Decision. Primary data was obtained by conducting a convenience survey with a sample size of 285 respondents using convenience sampling methods. This research is measured through scale variables, and is being analysed with Cronbach Alpha, factor analysis, and other tools to identify the most influential factors to the least one which will be input into the regression model. The findings are that there are four factors that impacting consumers' Green Purchase Intention in Jakarta, which are Green Attitude, Perceived Environmental Responsibility, Environmental Friendliness of Companies and Perceived Behavior Control.